Caracterização do itabirito dolomítico da Mina de Conceição, visando aproveitamento como matéria-prima na siderurgia - Julio Cesar Versiani Costa (2013)
The mineral and technological characterization is one of the most important tools in the definition for using a mineral resource in a structured and optimized way, being recommended from initial exploration to extraction stages. In the Conceição mine, located in Itabira, MG State, Brazil, and owned by Vale S.A., the dolomitic iron formations are treated as waste and are deposited in predefined permanent stock piles due to inability for processing and marketing this rock type, caused mainly by high CaO, MgO, P and Al2O3 contents. This work contributes to the development of an alternative use for the ferriferous dolomite ores as a flux in blast furnace burden or in the composition of pellets and/or sinter feed. Samples were collected and analyzed for particle size, chemical, mineralogical and microstructural properties. The major minerals identified in the global sample were hematite (abundant), dolomite (medium abundant), ankerite, magnesite and talc (low occurrence), lizardite and quartz (traces). Technological characterization tests demonstrated the feasibility of using the lump fraction (-32.00 +8.00mm) which exhibits good chemical quality, with low contents of SiO2 and Al2O3, and excellent values of tumbler and crepitation indices.